2014
DOI: 10.11158/saa.19.2.14
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bt+CpTI transgenic cotton on the performance of <em>Tetranychus</em><em> turkestani</em> (Acari: Tetranychidae)

Abstract: Transgenic cotton is very effective in controlling targeted pests such as cotton bollworm (Helicoverpa armigera). However, increases in spider mite (Acari: Tetranychidae) populations have been reported in fields of transgenic cotton. The objectives of our laboratory experiments were (i) to determine host plant preference (transgenic or non-transgenic cotton) of T. turkestani females and (ii) to compare the life table parameters of T. turkestani females reared on transgenic or non-transgenic cotton. Enzyme-link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…According to Rovenská et al (2005) T. urticae mites preferred transgenic plants for feeding and laying eggs relative to conventional plants. Li et al (2014) reported that mites Tetranychus turkestani Tetrtk, 1937 (Acari: Tetranychidae) preferred to feed and lay eggs in conventional plants than in transgenics. Few studies and the complexity of adequacy of the trials may be the reasons for variations in results and difficulty of comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…According to Rovenská et al (2005) T. urticae mites preferred transgenic plants for feeding and laying eggs relative to conventional plants. Li et al (2014) reported that mites Tetranychus turkestani Tetrtk, 1937 (Acari: Tetranychidae) preferred to feed and lay eggs in conventional plants than in transgenics. Few studies and the complexity of adequacy of the trials may be the reasons for variations in results and difficulty of comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…It is a candidate for augmentative biological control of the strawberry spider mite Tetranychus turkestani Ugarov and Nikolskii (Acari: Tetranychidae) on crop plants in greenhouses and fields in Khuzestan province, southwestern Iran, and elsewhere. Tetranychus turkestani is an important pest of crop plants in multiple families in the southwestern region of Iran (Mossadegh andKocheili 2003; Sohrabi andShishehbor 2008) and other countries including Russia (Popov 1981), USA (Jeppson et al 1975), China (Li et al 2014), India and some European countries (Migeon and Dorkled 2021). Characterized by frequent outbreaks coupled with acaricide resistance, this mite poses a threat to field and glasshouse crop producers (Sohrabi and Shishehbor 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Tetranychus turkestani Ugarov & Nikolskii (Acari: Tetranychidae) is an important pest of different field and glasshouse crops in the southwestern region of Iran (Mossadegh and Kocheili 2003), Russia (Popov 1981), USA (Jeppson et al 1975), China (Li et al 2014), India and some European countries (Zhang 2003). Characterized by frequent outbreaks coupled with acaricide resistance, this mite poses a threat to crop producers (Mossadegh and Kocheili 2003).…”
Section: Introductionmentioning
confidence: 99%